Plerixafor Successfully Rescues Poor Mobilizers Resulting in Adequate CD34 Cell Numbers However Stem Cell Products Yield Lower Numbers of CFU/CD34 and Delayed Neutrophil Engraftment - Szwajcer, David; Blankstein, Anna; Charette, Miranda M.; Guan, Qingdong; Wall, Donna A. (Blood, 2014)
Background: The CXCR4 inhibitor plerixafor was studied as a rescue agent in the setting of poor chemotherapy/filgrastim mobilization in a phase II trial of adults with lymphoma and myeloma who underwent a peripheral hematopoietic stem cell (HSC) mobilization prior to autologous transplant (ASCT) (NCT01037517). Given the wide range of expression of CD34 in myeloid precursors we were interested in the quality of the CD34 positive cells that were collected to proceed to transplant in poor mobilizers. Amongst a population of poor mobilizers would the CD34+ population contain cells of a more differentiated phenotype or express different proportions of homing receptors as CD34 cells collected from patients who mobilized easily? Methods: From 2009 to 2012 sequential adult patients with a diagnosis of lymphoma or multiple myeloma undergoing chemo-mobilization in preparation for autologous stem cell collection were enrolled on a phase II study to examine a strategy of plerixafor rescue in the setting of poor mobilization. Plerixafor (240 mcg/kg sc X 1) was administered on the evening prior to planned apheresis in subjects with a post nadir white blood cell count >1 X109/L and a peripheral blood [CD34] ≤ 10x106/L on the day prior to planned collection. Participants proceeded to stem cell apheresis the next day if their peripheral blood CD34 > 10x106/L. An aliquot from the mobilized product was analyzed for CD34+ cell subsets using markers of stemness ( CD33-, CD90, CD133 , CD166) and homing (CD26, CD49F, CD184) Differences between the groups are reported as means ±standard deviation and compared by two tailed t-tests. Results: 46/48 subjects were successfully mobilized in one day (HSC collection of >2 x 106 CD34+ cells/kg): 38 pts were not administered plerixafor (good mobilizer) and 8 pts were administered plerixafor (plerixafor rescue). The two participants not able to mobilize with plerixafor had evidence of progression of underlying disease within 2 weeks of attempted mobilization. Forty four participants (6/8 plerixafor and 38/38 good mobilizers) underwent ASCT. Median time to platelet engraftment was similar between good mobilizers (12 d, range 9-22d) and the plerixafor rescue group (13 d, range 12-13 d). The median time to neutrophil engraftment was prolonged in the plerixafor rescue group (23 d, range 17-67d) compared to good mobilizers (17 d, range 10-31d). CD34 content/kg of the apheresis product collected was similar between groups (good mobilizer 11.6±7.9 versus the plerixafor rescue group 6.4±4.6 p = 0.1). Subset analysis of CD34 positive cells in the products showed comparable expression of markers associated with more immature HSC progenitors but fewer CFU per CD34 positive cell plated. Homing receptors on the CD34 positive cells were similar despite the use of a CXCR4 inhibitor in the poor mobilizers. (See table) TableGood mobilizer N= 38 (Mean % ± SD)Plerixafor rescue N= 8 (Mean % ± SD)P valueStemmness MarkersCD90+ (Thy-1)24.4±12.730.6±19.30.3CD133+ (prominin1)59.1 ± 12.959.1 ± 16.80.9CD166+ (ALCAM)5.7±3.36.6±5.10.5CD33- (Siglec-3)80.6±3.369.8±13.10.01CFU/105 CD34+ cells1015±799276±3160.02Homing MarkersCD26 (dipeptidyl peptidase-4)5.4±410.4±13.30.05CD49F (VLA4)8.5±7.96.8±9.70.6CD184 (CXCR4)16.2±20.517.7±9.70.8 Discussion: Plerixafor used to rescue patients at risk of poor mobilization resulted in collection of adequate numbers of CD34+ cells for transplantation and allowed ASCT in a majority of poor mobilizers in our series. Delayed neutrophil recovery, was seen in the poor mobilizer cohort. We did not see a skewing of the CD34+ cells in the products from poor mobilizers to a more mature phenotype but did find lower clonogenic potency with fewer CFU generated/CD34 cells plated. Off Label Use: Plerixafor used as initial mobilization strategy in autologous stem cell mobilization.